PENDEKATAN M-APOS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KREATIF MATEMATIS SERTA HABIT OF TAKING RESPONSIBLE RISKMATEMATIKA SISWA - Rokhaeni, Arsinah (2014)
Penelitianinidilatarbelakangiolehhasil-hasilpenelitianterdahulu yang menunjukkanbahwakemampuanberpikirkritisdankreatifmatematissertaberanimengambilresikodalamkebiasaanberpikir (habits of mind) siswabelumsesuaidenganapayang diharapkan. Salah satupendekatanpembelajaran yang dapatditerapkanuntukmeningkatkankemampuanberpikirkritisdankreatifmatematissertahabit of taking responsible risk (HoTRR) matematikasiswaadalahpendekatan M-APOS.PenelitianinibertujuanuntukmenelaahpeningkatankemampuanberpikirkritisdankreatifmatematissertaHoTRRmatematikasiswamelaluipenerapanpendekatanpembelajaran M-APOS (Modifikasi APOS).Penelitianiniadalahkuasieksperimendenganmenggunakandesainpenelitiankelompokkontrol non ekuivalenuntukaspekkognitif, sedangkandesainperbandingankelompokstatikuntukaspekafektif.Penelitiandilakukanterhadap 80 siswakelas X SMA negeri di kotaCimahi. Instrumen yang digunakanmeliputiteskemampuanawalmatematis (KAM), teskemampuanberpikirkritismatematis, teskemampuanberpikirkreatifmatematis, skalaHoTRR, danlembarobservasi.Analisis data hasilpenelitianmenggunakanuji-t, uji ANOVA satujalur, danujischeffeuntukujistatistikparametrik, sedangkanujiMann-Whitneyuntukujistatistiknonparametik.Berdasarkanhasilanalisistersebut, diperolehkesimpulanbahwapeningkatankemampuanberpikirkritismatematissiswa yang mendapatpembelajarandenganpendekatan M-APOS (PM-APOS) lebihbaikdaripadasiswa yang menggunakanpendekatankonvensional (PK) berdasarkankesuluruhanmaupunkategori KAM siswa, kecualipadakategorirendah,peningkatankemampuanberpikirkreatifmatematissecarakeseluruhanmaupunberdasarkankategori KAM (tinggi, sedang, rendah) siswapadakelas PM-APOS lebihbaikdaripadasiswakelas PK,terdapatperbedaanpeningkatankemampuanberpikirkritisdankreatifmatematispadakelas PM-APOS,dantidakterdapatperbedaanpencapaianHoTRRmatematikasiswaantarakelas PM-APOS dankelas PK. The research was grounded by the results of previous research which showed that critical and creative thinking ability and students' habit of taking responsible risk in mathematics habits of mind are not as expected. One of learning approach for enhancing mathematical critical and creative thinking ability and students' mathematics habit of taking responsible risk (one of habits of mind) is M-APOS learning approach. This study examines the enhancement of students' mathematical critical and creative thinking ability and students' mathematic habit of taking responsible risk (HoTRR) through the application of M-APOS learning approach (Modified-APOS). Through a quasi experiment with non-equivalent control group design for the cognitive ability and static group comparison for the affective ability. This study involved 80 ten-grade students from a senior high school in the city of Cimahi. Instrument of the study consist of a set of mathematical prior ability (MPA) test, a set of mathematical critical thinking ability test, a set of mathematical creative thinking ability test, a set of Mathematic HoTRR scale and observation. Data are analyzed by using t-test, one-way ANOVA, and Scheffe test for parametric test and Mann-Whitney test for the nonparametric test. The study finds that the enhancement of students' mathematical critical thinking ability who get PM-APOS is better than those who get conventional learning approach (PK) viewed from the whole students and all MPA group students, except at low MPA group students; the enhancement of students' mathematical creative thinking ability who get PM-APOS is better than those who get PK viewed from whole students and all MPA (upper, middle, lower levels) group students; there are differences enhancements of students' mathematical critical and creative thinking ability who get PM-APOS; and there aren't differences students' mathematic HoTRR between who get PM-APOS and those who get PK.